FORMATION OF AN APPROACH TO ENSURING INNOVATIVE-DRIVEN PROGRESSION OF INDUSTRIAL ENTERPRISES UNDER THE CONDITIONS OF DIGITALIZATION AND SUSTAINABLE DEVELOPING - KOROTAIEVA, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2025)
It has been established that under the conditions of digitalization of the economy, sustainable development, industrial enterprises have faced the issue of increasing competitiveness, improving performance indicators due to the intensification of competition. The emergence of digital innovative technologies preconditions their research and implementation at enterprises. It has been determined that the prerequisite for intensification of innovation processes is the formation of trend-setting activity through the introduction of a strategy for ensuring innovative activity. It has been proven that the establishment of innovative activity processes will make it possible to increase the efficiency of innovative activity, will contribute to the development of innovations and the innovative development of the enterprise as a whole. It was found that the innovative development of an enterprise affects the formation of competitive advantages, rationalization of resource use and cost reduction, coverage of new product sales markets, increasing investment attractiveness, adherence to the principles of sustainable development, financial indicators, profitability. The importance of ground-breaking development is proven, since industrial enterprises that do not develop and implement pacing technologies may lose competitive positions. The approach to ensuring the ground-breaking development of industrial enterprises has been improved, which defines a sequence of stages, the implementation of which will allow restoring innovative processes, contributing to the activation of innovative development, and will also allow achieving financial and innovative effects, ensuring sustainable growth in the conditions of digitalization of the economy. An innovation cycle has been formed, which includes a set of elements that affect the innovative development of industrial enterprises. The specified innovation cycle makes it simple to establish a close relationship between impact factors, the strategy of innovative activity, the level of innovative activity, innovative practice and innovation management, as well as to determine their impact on achieving financial and innovative effects.